Coal prices as a dominant factor in stock return models: an empirical study of coal mining companies on the indonesia stock exchange - Sri Retnaning Sampurnaningsih; Arum Indrasari; Maya Sova; Luqman Hakim (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to analyze and address the inconsistencies in previous research results and explain the phenomenon of Market Appreciation that differs from the theory of Efficient Capital Markets. This is what prompted the researcher to do this by using a combination of time series and cross-sectional data. This type of research is quantitative with a multiple regression analysis method of panel data with a sample of 25 coal mining sub-sector companies listed on the Indonesia Stock Exchange (IDX) for seven years. The formula in this study, maximizes the value of Market Appreciation through the Company's Capital Structure as an intervening variable and by using companies on the IDX as the research object. Two research models are integrated into one and each through model selection testing, Chow Test, Hausman Test, and Lagrange Multiplier Test. The results of the first research model; that the interest rate is the dominant variable that is most sensitive to impacting capital structure, while the results of the second research model; that market appreciation is largely determined by the dominant exogenous variable that is most sensitive to coal prices. It is hoped that these results can be a reference for investors on the Indonesia Stock Exchange to maximize stock returns.